Making a servomechanism control for the spatial variation characterization of semiconductors materials applying photoreflectance technique (Revista de Investigaciones Universidad del Quindío, 2017)
This study is about the electronic automation of the photoreflectance technique (PR), which consisted of the development of a digital electronic control for the spatial variation characterization of semiconductor materials. In this type of optical characterization, the interaction of radiation with the matter is achieved by directing two beams of light toward the sample, using arrays of mirrors and lenses, which require precise optical alignment. For this reason, a servomechanism for digital control of the positioning of the sample was added to the optical path , fixing the incident area of the light beams, allowing moving the sample in the XY coordinate system under study, obtaining 1.0 μm of resolution for both axes. The digital control of the position of these beams of light in the sample was achieved by embedding an electronic system based in AVR microcontroller, and a graphical user interface developed in LabVIEW software from the National Instruments. In the calibration of the measuring system, we used GaAs commercial single crystals, which are able to reproduce physical information reported in the literature for this material and therefore be able to contribute with this study to increasing the versatility of the PR technique.
Keywords: Photoreflectance; Mapping Characterization; GaA; automation; servomechanism